Characteristics of Cold-Setting Adhesive Derived from Waste Styrofoam for Bonding Laminated Gmelina (Gmelina arborea) Wood - Karliati, Tati; Dungani, Rudi; Hadiyane, Anne; Hidayat, Wahyu; Lubis, Muhammad Adly Rahandi (Department of Forestry, Faculty of Agriculture, University of Lampung, 2025)
Developing cold-setting adhesives derived from waste styrofoam (WS) of expanded polystyrene foam for laminated gmelina wood involves innovative recycling of WS into functional adhesives. As a type of thermoplastic polymer, WS can be used as an adhesive at room temperature. In this study, WS was functionalized into cold-setting adhesives through dissolution and cross-linking reaction with methylene diphenyl diisocyanate (MDI) at a concentration of 40% w/v at 60°C. The mixture was then stirred at 200 rpm for 30 minutes. The adhesive is characterized by its ability to be set at room temperature, offering environmental benefits and practical applications in wood lamination. Solids content, gelation time, viscosity, cohesion strength, functional group analysis, morphological features, and curing temperature analysis were performed to characterize the cold-setting adhesives. The WS-MDI-40% had 62.4% solids content, 906.8 mPa.s viscosity, 182.3 Pa cohesion strength, and 197.8 minutes of gelation time at room temperature. The adhesion performance was evaluated in laminated wood using gmelina wood at glue spread rates of 250 and 300 g/m2 and cold-pressed at various durations. The block shear strength value of laminated wood bonded with WS-MDI-40% at 300 g/m2 and cold-pressed for 24 hours was higher than that of other samples, reaching 8.2 MPa, which met the Japanese Agricultural Standard (JAS No. 234) for glued laminated timber, exceeding the minimum requirement of 5.4 MPa. Fourier transform infrared (FTIR) spectroscopy revealed that the cold-setting WS-MDI-40% were cross-linked via urethane linkages (R–NH–COO–R). The free –N=C=O groups could react with the –OH groups of gmelina wood to produce laminated wood during cold-pressing. This study suggested a recycling alternative of WS into a cold-setting wood adhesive for laminated wood, which can be utilized in interior applications. Keywords: adhesive, block shear strength, cohesion strength, cold-setting, gmelina wood